Tuberculosis patients with special clinical conditions treated with contezolid: three case reports and a literature review - Wang, Jun; Ma, Liping (Frontiers in Medicine, 2023)
Background: Contezolid is a noval oxazolidinone antibacterial agent, but there have been no reports of any pertinent clinical studies for the treatment of tuberculosis (TB). This was the first report of three TB patients who were successfully treated with contezolid. Case Presentation: One case was TB complicated with myelosuppression syndrome. One case was drug-resistant TB complicated with cirrhosis and anemia. And another case with drug-resistant TB complicated with liver transplantation developed severe anemia after linezolid treatment. Following contezolid therapy, the three patients' symptoms essentially got better, and no adverse reactions were observed. The chest computed tomography (CT) examination also indicated that the therapeutic effect of this anti-TB regimen was in line with expectations. Conclusion: Contezolid showed good efficacy and fewer side effects in the treatment of TB. It may be a promising treatment drug for TB.